The Effect of Wood Charcoal Powder and Pumice Powder on The Parameters of Shear Strength of Clay Soil - Raisya Fithria; Dyah Pratiwi Kusumastuti (Indonesian Geotechnical Journal, 2022)
Soil as a foundation must have sufficient bearing capacity when receiving the load acting on it. However, not all soil types have these characteristics, especially soft clay. The problems encountered in soft clay for construction are generally large settlements and low bearing capacity. Overcoming the problem of lack of bearing capacity in soft clay can be done with improvements. A simple improvement is done by the chemical stabilization method. Chemical stabilization is carried out by mixing soft clay and other materials such as pumice powder and wood charcoal powder. Variations in the addition of these materials in the study were 2% and 4% pumice powder and 15%, 20%, and 25% wood charcoal powder. Based on the test results, it was found that the increase in pumice powder and wood charcoal powder caused changes in physical and mechanical parameters in the soil sample. For physical parameters due to the addition of pumice powder and wood charcoal powder, the water content and liquid limit values ​​decreased, while the specific gravity values, plastic limits, and shrinkage limits in the soil samples increased compared to the original soil samples. Meanwhile, the mechanical parameters in terms of the unconfined compressive strength test, due to the addition of pumice powder and wood charcoal powder caused the value of the unconfined compressive strength (qu) and the undrained shear strength (su) to increase. The biggest change in the parameters of the unconfined compressive strength and undrained shear strength of the soil sample was found in the addition of 4% pumice powder and 25% wood charcoal powder with an increase of 15.58% compared to the original soil sample.